Proceedings of the Thirty-First SIGCSE Technical Symposium on Computer Science Education 2000
DOI: 10.1145/330908.331846
|View full text |Cite
|
Sign up to set email alerts
|

Empirical results of a software engineering curriculum incorporating formal methods

Abstract: A three year study of integrating formal methods into the undergraduate software engineering curriculum of the Systems Analysis Department of Miami University was recently completed (NSF Educational Innovation Program CDA-9522257). Formal analysis skills were added to the curriculum to address the concern that the discipline of software engineering education lacks sufficient emphasis on mathematics and engineering science. A presentation of the six courses chosen for integration of formal analysis is given. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The investigators observe that the formal methods group's solutions are "far more correct than the nonformal solutions." Additional details appear in a second paper, hereafter called the "Inroads paper," authored by only Sobel [4].…”
Section: Overview Of Published Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators observe that the formal methods group's solutions are "far more correct than the nonformal solutions." Additional details appear in a second paper, hereafter called the "Inroads paper," authored by only Sobel [4].…”
Section: Overview Of Published Papermentioning
confidence: 99%
“…The students in this group volunteered for a tougher curriculum: They were willing to take two extra courses, "Introduction to Program Derivation" and "Formal Analysis of Concurrent Programs." 4 Furthermore, the data structures course required more time than others because of the additional effort needed for studying and writing specifications. The Inroads paper says about the formal version of the data structures course (p. 159):…”
Section: Differences In Motivationmentioning
confidence: 99%
“…A number of authors have suggested integrating SE concepts into introductory programming courses [9]. We also support the idea of introducing ideas at an earlier stage.…”
Section: Why Not Se In Another Course?mentioning
confidence: 52%
“…These are not impossibly vague goals: Sobel's study [84], albeit the subject of a debate on experimental design [85,86], was a first attempt to assess whether a training in formal techniques may improve students' general analytic and problem solving skills [87]. In our teaching [88], with its origins in industrial courses, we have been led to ask whether we really know what skills we want to help our students develop and how we could establish whether our current courses are achieving this.…”
Section: Aimsmentioning
confidence: 99%